A Case of Respiratory Syncytial Virus Infection in an HIV-Positive Adult - Aakriti Gupta; Purav Mody; Shefali Gupta (Case Reports in Infectious Diseases)
Respiratory syncytial virus (RSV) is commonly known to cause an influenza-like illness. However, it can also cause more severe disease in young children and older adults comprising of organ transplant patients with immunocompromised status. Till date, only four cases of RSV infections have been reported in HIV-positive adults. We describe here a case of HIV-positive female with relatively preserved immune function who presented with RSV infection requiring ventilation and showed improvement after prompt treatment with intravenous immunoglobulin.